Efforts to Improve Early Childhood Cognitive Skills through Literacy (Research at the Mahardika Dewasari Kindergarten in Cijeunjing, Ciamis) - Imas Heryani; Nurjanah Nurjanah; Desi Suryani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Cognitive development is a crucial aspect of early childhood growth and development that needs to be stimulated from an early age. One effective way to optimize cognitive development is through literacy activities. Literacy encompasses not only the ability to read and write but also involves understanding symbols, language, and the meaning of everyday experiences. This study aims to describe efforts that can be made to improve the cognitive development of early childhood through literacy activities within the family environment and educational institutions. The method used was a literature review, reviewing various literature related to early childhood education and literacy. The results of the study indicate that literacy activities such as reading stories, providing play-based literacy reading corners, and directed digital literacy can stimulate children's thinking, language, and problem-solving skills. Therefore, collaboration between teachers and parents is crucial in creating a conducive and sustainable literacy environment.